Analisis Kecerdasan Interpersonal pada Anak Usia 5-6 Tahun di TK Jamil Hasan - Nazila Najmi Hayati; Srinahyanti (JURNAL BUNGA RAMPAI USIA EMAS, 2025)
The human perspective regarding intelligence at this time is only limited to academic intelligence which is measured through IQ. Gardner challenges this by stating that intelligence is not unique. There are several abilities that are really needed in the 21st century, one of which is the ability to collaborate and communicate. These two abilities are related to interpersonal intelligence. Of the several kindergartens that researchers have visited, Jamil Hasan Kindergarten has a vision, mission and goals related to interpersonal intelligence, so researchers want to see how interpersonal intelligence forms in children aged 5-6 years at Jamil Hasan Kindergarten and how efforts are made to develop interpersonal intelligence in Jamil Hasan Kindergarten. The research method used is qualitative using a descriptive approach and data collection techniques through observation, interviews and documentation. Based on this research, it can be seen that the aspect that appears in every child aged 5-6 years at Jamil Hasan Kindergarten is the aspect of queuing and mustiness that appears most rarely in children, namely the ability to socialize, interact and adapt to the environment or new friends